The Brauer-Manin obstruction for sections of the fundamental group - Stix, Jakob (Journal of pure and applied algebra, 2011)
We introduce the notion of a Brauer-Manin obstruction for sections of the fundamental group extension and establish Grothendieck’s section conjecture for an open subset of the Reichardt-Lind curve.